Modeling & Simulation for West Qurna (Tuba-1) Cathodic Protection Design by using MATLAB Simulink - Abdulaaima, Dhuha A.; Omara, Waleed I.; Kadhim, Raaed J.; Ibrahim, Buthaina K.; Abdulkareem, Mays M.; Shehadha, Mohammed A. (Journal of Petroleum Research and Studies, 2022)
Abstract This study focused on the two systems of Cathodic Protection, CP, (temporary (Sacrificial Anodes, SACP) & permanent (Impressed Current, ICCP) that were used to protect West Qurna (Tuba-1) crude oil pipeline42 in / Basrah Oil Company, BOC, from corrosion challenges. Design Calculations for CP systems were achieved according to the standards of National Association of Corrosion Engineers, NACE. These calculations were simulated using Matlab –Simulink Software 2018. Then, the simulated design was converted to Graphical User Interface, GUI. This GUI allows the user to enter the design data & perform the calculation faster & more efficiently. Furthermore, GUI was converted into a dependent program by installing Matlab Runtime Installer which enables the execution of Matlab files on computer without installed version of Matlab. The results showed that there was matching between the calculations of CP design & the simulated design. SACP demonstrated that 4 Mg anodes are required to protect 1 km of sec.1 of pipeline for 4 years period while 6 Mg anodes are required to protect 1 km of sec.2 for 11 years period. ICCP system for sec.1 of pipeline requires 4 magnetite anodes to supply 2.86 v by rectifier in accordance with horizontal bed resistance RH ≤ 1.5 Ω while sec.2 requires 25 magnetite anodes to supply 2.45 v by rectifier in accordance with vertical bed resistance Rv ≤ 1.5 Ω. The designed program proved that it was easy to install & efficient in making Calculations. According to the above, this program can be adopted in prediction studies to know the design outputs (No. of anodes, required current for protection & voltage supplied by rectifier).